The Privilege of Working From Home at the Time of Social Distancing - Armanda Cetrulo; Dario Guarascio; Maria Enrica Virgillito (Intereconomics)
Abstract Although the common perception is that the pandemic is ‘the great equaliser’, workers’ tasks, contractual framework and position in the internal organisational hierarchy strongly affect their ability to work remotely.